Indonesian Students' Scientific Literacy in Islamic Junior High School - Ramli, Munasprianto; Susanti, Baiq Hana; Yohana, Media Putri (International Journal of STEM Education for Sustainability, 2022)
Scientific literacy is one of the main and key aspects of facing various challenges in the 21st century. Building students' scientific literacy does not mean making every student a future scientist. However, this is more about building their knowledge of science and technology to play a role in making choices that impact the survival of life today and in the future. This study aimed to analyze the scientific literacy skills of Islamic Junior High School students in Indonesia by using PISA questions from the previous year and finding out their perceptions of PISA academic literacy questions. This study used a sequential explanatory research method with a mixed quantitative and qualitative approach. A total of 150 students from eight Islamic Junior High Schools in West Sumatra and DKI Jakarta Provinces in Indonesia were selected using a purposeful sampling technique. The instruments used are scientific literacy tests to collect quantitative data, interview guides, and open questionnaires for qualitative data. The quantitative data obtained were analyzed by descriptive statistics, while the qualitative data were analyzed by thematic analysis. The results show that the science literacy score of Indonesian Students in Islamic Junior High schools value of Islamic Junior High School students is lower than the average value of the OECD countries and the United States. Then, the students also thought that the scientific literacy questions tested were difficult because they rarely got similar questions. This results also suggest that several factors cause the low literacy scores of Islamic junior high school  students, namely their lack of habit of working on similar questions, the limited number of teachers in giving questions that promote critical and analytical thinking skills and the low desire of students to read and explore knowledge other than what they get in school.